Archaeozoological material from the Late Antique fortified settlement near the modern-day town of Dimovo, northwestern Bulgaria - Zlatozar Boev; Alexander Manev; Alexander Harizanov; Ivaylo Dedov (Българско е-Списание за Археология)
In 2022–2023, a complete rescue archaeological excavation was carried out at the Late Antique fortified settlement (the late 4th–6th c. AD) discovered in 2021 near the modern-day town of Dimovo (Vidin Region, NW Bulgaria). A total of 14,045 fragments of animal remains representing 50 taxa were identified from these two field seasons. Along with animal husbandry, hunting still had a significant place. Some wild mammals (such as wild boar, Еuropean hare, red deer, roe deer, fallow deer, aurochs, and European bison) were hunted for food, while others (such as red fox, wild cat, grey wolf, brown bear, and beaver) were hunted for their fur. Livestock breeding (cattle, sheep, goat, horse, donkey and pig) was the basic source of meat, transportation, or harnessing for agriculture. Interestingly, numerous remains of Greek/Hermann’s tortoises have been found, which hints that this species’ meat was also used for food. A large set of bone and antler finds bears traces of different stages of processing, indicating that some animals were used as a source of raw material for the production of crafted items. Wild birds, albeit in significantly smaller amounts, were represented by the great bustard, mute swan, graylag goose, lesser white-fronted goose, grey partridge, grey heron, common woodpigeon, common buzzard, white-tailed sea-eagle, rook, and the disappeared black grouse. The wild faunal diversity around the settlement was much richer than it is today. About 1/10 of the established animal composition are species that have disappeared in the last millennium from the modern fauna of Bulgaria – Eurasian black grouse, great bustard, aurochs, wisent and Eurasian beaver.